UNDERSTANDING ADVANCE CARE PLANNING IN AN ACTIVE LIFESTYLE RETIREMENT COMMUNITY. (16th November 2018) - Roberts, M; Sappington, E; Lowenkron, J; VandeWeerd, C; Yalcin, A; Roth, D
Abstract: Advance care planning has been demonstrated to enhance completion of advance directives (Detering et al., 2010) and increase patient-centered outcomes (Sullivan & Slatore, 2015). Care received at the end-of-life may not match desired care if the proper advance directives are not set in place and maintained to reflect changing priorities, often impacting quality of life (Lewis et al., 2016). This study aimed to investigate the adoption and coordination of ACP's within an active lifestyle community. Preliminary care support data are presented from an on-going clinical trial to better understand older adult's brain health: BNA Reference Database & Longitudinal Registry of the Normal and Pathological Aging Brain project from 8/30/2017–8/21/2018. Research takes place in The Villages, FL a planned retirement community of over 120, 000 residents. Self-report data from 1066 participants indicated that 76.9% had an ACP, 79.3% had a proxy decision maker or power of attorney, and 94.7% had an available family member or friend to care for them if seriously ill. Older participants were more likely to have an ACP (F(1, 1063) = 17.68, p < .001) and POA (F(1, 1063) = 15.55, p < .001). Most (82.6%) reported that their ACP's had been updated in the last 5 years (Avg. 3.6 SD 4.3). Despite high utilization rates, only 42.7% of participants stated their primary medical provider and POA possess current copies of their ACP's. Like other populations, targeted programs and policies are needed to encourage up-to-date and coordinated ACP's to enhance quality of life at the end-of-life (Harrison et al., 2016).